The influence of structural design methods on the embodied greenhouse gas emissions of structural systems for tall buildings. (April 2020) - Helal, James; Stephan, André; Crawford, Robert H.
Abstract: The construction of tall buildings generates a high spatial and temporal concentration of greenhouse gas (GHG) emissions. Research has shown that as building height increases, more resources per floor area are required to withstand the increasing effects of wind and earthquake loads. This has major implications for the environmental performance of tall buildings since the embodied GHG emissions (EGHGE) of structural systems tend to represent the greatest portion of the life cycle EGHGE of tall buildings. In mitigating the effects of climate change, life cycle assessment (LCA) has been proposed as an early stage design tool to facilitate the choice of structural systems and materials for tall buildings. Existing studies that use LCA to compare alternative structural systems and materials use incomplete and inconsistent structural design methods related to imposed loads, façade loads and lateral loads, both static and dynamic in nature. The aim of this paper is to demonstrate the influence of these structural design methods on the EGHGE of structural systems for tall buildings. The influence of structural design methods on the EGHGE of structural systems for tall buildings are evaluated using a total of 80 structural systems, parametrically designed using finite element modelling. A hybrid life cycle inventory analysis method is used to quantify the EGHGE of the structural systems. The paper demonstrates that structural design methods can significantly influence the values of EGHGE of structural systems for tall buildings, by up to 22%. The findings of this study confirm the need for clarity, consistency, transparency and comprehensiveness in structural design methods when conducting comparative LCA studies of structural systems for tall buildings.